Missional view of the Good Samaritan parable in handling neighbourliness in Christ’s view - Muswubi, Takalani A. (Verbum et ecclesia, 2025)
Diverse perspectives, be it, theoretical or theological, of the parable of the Good Samaritan, have shaped the mainstream thinking and practices of the global community (that is, global and local churches and communities). Many relief and developmental programmes were shaped, influenced and motivated by Jesus’s parable of the Good Samaritan. The double-sided question about attaining God’s Kingdom and who my neighbour is remains the relational challenge of loving God and loving others, respectively - the whole mark of law and life. Loving God and loving others is a missional call, which should be expressed in handling the issue of neighbourliness. To do so, the question is: what the motive of Jesus’s parable of the Good Samaritans is? This article is set to discuss the selfless love versus the self-righteous love uncovered in the parable of the Good Samaritans using the three main schools of thought, which represent the three Rules that govern human relationships namely, the Iron Rule, the Silver Rule and the Golden Rule. Intradisciplinary and/or interdisciplinary implications: The article is adding a voice to the ongoing debate about the main message, motive and missional call behind the parable of the Good Samaritans. The selfless love as opposed to self-centred and selfish love is not only in demand in the socio-economic and political policies and practices but also should find its concrete expression in handling the issue of neighbourliness among those who are marginalised and underprivileged in South Africa and beyond.